Representation of Racism In Dolce & Gabbana Advertising - Retno Dyah Kusumastuti; Alfonsius Hasiholan; Emir Mirza (International Journal of Business Studies, 2023)
Petty (2002) in his article states that an advertisement should be responsible for being able to play a positive and useful role. This study aims to analyze an advertisement that represents the elements of racism contained in the Dolce & Gabbana: DG Loves China advertisement, using Roland Barthes' semiotic analysis model. In this study, the researcher used exploratory descriptive research with a qualitative approach. Descriptive research aims to describe a certain symptom. Operationally, this research uses the semiotic method to analyze the research object. The object of this research is the Dolce & Gabbana: DG LOVES CHINA advertisement in video ad format. Based on an analysis using the Roland Barthes method, the Dolce & Gabbana: DG Loves China advertisement represents racism because there are elements that are considered to be degrading the ornaments inherited by the Chinese people which are considered important and have special meaning for the Chinese people (Ban & Lovari, 2021). In connotation, the advertisement for Dolce & Gabbana: DG Loves China, by showing a model with a Chinese ethnic background, offends the Chinese ethnicity with representations of racism interpreted by the audience.